Draft proposal to facilitate the receipt and kissing of black stone for pilgrims and worshipers - Morsy, Mohamed Hanafy Abdullah (Arab Journal for Sciences and Research Publishing, 2024)
The aim of this research is to provide innovative solutions to facilitate the access of pilgrims and worshippers to the Black Stone and kissing it, thereby enhancing their religious experience. Kissing the Black Stone during Tawaf is considered a recommended Sunnah that reflects the pure following of the Prophet Muhammad (peace be upon him) and embodies the servitude of Muslims and their reverence for the rituals of Allah. Despite the spiritual significance of this act of worship, the heavy crowding around the Black Stone remains a major obstacle, potentially preventing many, especially women, the elderly, and those with limited physical abilities, from performing this ritual. The research includes a project proposal to facilitate the process of receiving the Black Stone for at least 10,000 pilgrims daily, ensuring a smooth and safe experience. The project suggests using innovative strategies, including establishing an organized queue system to manage the flow of pilgrims, along with constructing an underground tunnel extending from a hall outside the Tawaf area to the Black Stone, transforming the crowding into a safer space. A revolving door mechanism will be implemented to organize entry and exit, and the "Nusk" app will be used for electronic booking, in addition to surveillance cameras to manage crowds in real-time. These solutions are integrated to reduce congestion and enhance safety, with the tunnel entrance located outside the Tawaf area. Live video analysis will provide information on optimal flow rates, while security forces monitor the system to avoid crowding. The implementation of these solutions is expected to significantly improve accessibility, allowing more pilgrims to perform the ritual smoothly and safely, enhancing their overall experience.
Keywords: Pilgrimage Optimization; Black Stone Access; Tawaf Facilitation; Pilgrim Safety; Crowd Control; Pilgrimage Infrastructure